2022
DOI: 10.1177/08948453221133831
|View full text |Cite
|
Sign up to set email alerts
|

Decent Work and Turnover Intentions Among Chinese Millennials: A Longitudinal Study

Abstract: Turnover among millennial employees is frequent and is more common when work is not considered decent. Nevertheless, the potential reasons for why decent work attainment links with millennials’ turnover intentions deserves further exploration. Grounded in the psychology of working theory and social exchange theory, the current research explored the roles of overall well-being and perceived career opportunity in the relation between decent work and turnover intentions. Through an analysis of three-wave data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…Recently, the indirect effect of job satisfaction between decent work and turnover intention has been reported among new-generation workers (Wan & Duffy, 2022) and was also confirmed among the sample of blue-collar workers in our study. Nevertheless, our replication of such a finding among employees in a non-western country is noteworthy, given the context of South Africa.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Recently, the indirect effect of job satisfaction between decent work and turnover intention has been reported among new-generation workers (Wan & Duffy, 2022) and was also confirmed among the sample of blue-collar workers in our study. Nevertheless, our replication of such a finding among employees in a non-western country is noteworthy, given the context of South Africa.…”
Section: Discussionsupporting
confidence: 88%
“…Against the backdrop of the PWT, decent work has been related to job satisfaction, withdrawal intention, and life satisfaction, all of which are often described as well-being or work fulfillment outcomes (Buyukgoze-Kavas & Autin, 2019;Di Fabio & Kenny, 2019;Dodd et al, 2019). More recent studies have also shown that decent work positively influences overall well-being, commitment, and work engagement McIlveen et al, 2021) and negatively influences turnover intention (Wan & Duffy, 2022a;2022b) and physical and mental health (Duffy et al, 2019).…”
Section: The Present Studymentioning
confidence: 99%
“…On one hand, this observation may be linked to the distinct work values and employment preferences of the millennial generation, highlighting a shift in priorities beyond merely seeking high income [ 39 ]. Millennials often prioritize factors such as having sufficient free time and aligning with their personal life values in their work [ 40 ]. On the other hand, these trends may be attributed to the relatively lower remuneration [ 41 ], lack self-confidence, sufficient work experience and problem-solving skills [ 42 ], and the young nurses' lack of firmly established professional identity [ 43 ], which are commonly associated with younger nurses and may compromise their perception of work decency.…”
Section: Discussionmentioning
confidence: 99%
“…Although the variables were positioned according to theory, longitudinal studies would be needed to confirm these findings. There have been several recent attempts to study these constructs across time, namely looking at how decent work predicts meaningful work, turnover intentions, and physical health (e.g., Allan et al, 2020; Duffy et al, 2021; Wan & Duffy, 2022). These studies have generally shown decent work to significantly predict these variables across time, but more work is needed to tease apart the bi-directional relations amongst this group of constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on the links between decent work and more distal work outcomes, such as job satisfaction, meaningful work, turnover intentions, and mental and physical health. These studies have also shown strong links between experiencing one's work as decent and being satisfied and stable in one's job; it appears that decent work also links to stronger levels of general and physical mental health (Allan, Tebbe, et al, 2019;Duffy et al, 2021;Huang et al, 2022;Kim & Kim, 2022;Wan & Duffy, 2022).…”
Section: Psychology Of Working Theorymentioning
confidence: 93%